Mercury bioavailability, transformations, and effects on freshwater biofilms. (19th September 2017) - Dranguet, Perrine; Le Faucheur, Séverine; Slaveykova, Vera I.
Abstract: Mercury (Hg) compounds represent an important risk to aquatic ecosystems because of their persistence, bioaccumulation, and biomagnification potential. In the present review, we critically examine state‐of‐the‐art studies on the interactions of Hg compounds with freshwater biofilms, with an emphasis on Hg accumulation, transformations, and effects. Freshwater biofilms contain both primary producers (e.g., algae) and decomposers (e.g., bacteria and fungi), which contribute to both aquatic food webs and the microbial loop. Hence they play a central role in shallow water and streams, and also contribute to Hg trophic transfer through their consumption. Both inorganic and methylated mercury compounds accumulate in biofilms, which could transform them mainly by methylation, demethylation, and reduction. Accumulated Hg compounds could induce diverse metabolic and physiological perturbations in the microorganisms embedded in the biofilm matrix and affect their community composition. The bioavailability of Hg compounds, their transformations, and their effects depend on their concentrations and speciation, ambient water characteristics, biofilm matrix composition, and microorganism‐specific characteristics. The basic processes governing the interactions of Hg compounds with biofilm constituents are understudied. The development of novel conceptual and methodological approaches allowing an understanding of the chemo‐ and biodynamic aspects is necessary to improve the knowledge on Hg cycling in shallow water as well as to enable improved use of freshwater biofilms as potential indicators of water quality and to support better informed risk assessment. Environ Toxicol Chem 2017;36:3194–3205. © 2017 SETAC